Biomechanical effects of the working modes of LVADs on the aortic valve: A primary numerical study. (September 2020) - Gao, Bin; Zhang, Qi
Highlights: Although a growing number of patients undergo LVAD implantation for heart failure treatment, the aortic valve diseases caused by LVADs support have attracted more and more attentions. However, the biomechanical effects of working modes of LVADs on the aortic valve are still poor understood. This manuscript investigate the different biomechanical effects of three kinds of working modes (namely, constant flow mode, the co-pulse mode and the counter pulse mode) of LVAD on the aortic valve by using a novel fluid-structure interaction method, which combines the lattice Boltzmann method and finite element method together. The numerical study shows that the working mode of LVADs is an important factor, which could directly change the biomechanical states of the aortic valve and the hemodynamic environment in the aortic root. Compared with the constant flow mode, co-pulse and counter pulse working modes could provide better biomechanical effects on the aortic valve. However, the advantages of the two working mode on valve lobe are not the same. The co-pulse mode is more suitable for patients with certain cardiac function, keeping the valve open intermittently while reducing the pressure load on the aortic leaflets during the diastolic phase to prevent valve remodeling. In contrast, the counter pulse mode is more suitable for the patients with severely impaired cardiac function, while providing greater blood perfusion, keep the valve open as much as possible. This manuscript is a follow-up study of the previous study, titled "Hemodynamic effects of support modes of LVADs on the aortic valve". The previous study only reported that the pulsatile support mode of LVAD could provide better biomechanical states to the aortic valve. However, the different effects of various support modes (such as co-pulse mode, counter pulse mode) on the aortic valve are not reported. This is the aim of this study, to compare the different biomechanical effect of two widely studied support modes of LVAD, namely the co-pulse mode and the counter pulse mode, on the aortic valve. The results of this study could provide more useful information to the doctor to choose appropriate support mode. Abstract: Aortic valve diseases caused by the support from left ventricular assist devices (LVADs) have attracted increasing attention due to the wide application of the LVADs. However, the biomechanical effects of the working modes of LVADs on the aortic valve are still poorly understood. Hence, in this study, these biomechanical effects are investigated using a novel fluid–structure interaction method, which combines the lattice Boltzmann and the finite element methods. On the basis of the clinical practice, three working modes of LVADs, namely, the constant flow, co-pulse, and counter pulse modes, are chosen. Results demonstrate that the working mode of LVADs is an important factor as it can change the biomechanical states of the aortic valve and the hemodynamic environment in the aortic root directly. Compared with the constant flow mode, the two other working modes can provide better biomechanical effects on the aortic valve. However, the advantages of the co-pulse and the counter pulse modes on the aortic valve are not the same. The LVADs in the co-pulse mode can remarkable reduce the pressure load of the leaflets during the diastolic phase (maximum stress: co-pulse mode, 0.85 MPa; constant flow mode, 1.23 MPa; counter pulse mode, 1.50 MPa). By contrast, the LVADs in the counter pulse mode can achieve the highest effective orifice area of the aortic valve (co-pulse mode: 0.12 cm 2, constant flow mode: 0.17 cm 2, counter pulse mode: 0.25 cm 2 ). In sum, the co-pulse mode is suitable for patients with certain cardiac function, because this mode keeps the valve open intermittently and reduces the pressure load on the aortic leaflets during the diastolic phase to prevent valve remodeling. By contrast, the counter pulse mode is suitable for patients with severely impaired cardiac function, because this mode keeps the valve open as much as possible and provides high blood perfusion.